Delayed Erosion of a Pelvic Reconstruction Plate into the Bladder Causing Recurrent Urinary Tract Infections: A Case Report. Issue 4 (11th November 2015) - Babu, Jacob; Shah, Kalpit N.; Mansuripur, Kaveh P.; Hayda, Roman
Abstract : Case: : A forty‐seven‐year‐old woman presented with recurrent urinary tract infections eleven years after open fixation of a pelvic ring injury. Cystoscopy revealed that the pelvic reconstruction plate had eroded into the bladder, likely the source of the recurrent infections. Following removal of the involved pelvic hardware and repair of the bladder, the patient had no further urinary tract infections. Conclusion: : Operative fixation of osseous pelvic injuries places metal implants in proximity to the bladder. Late erosion of hardware into the bladder can occur. A low threshold for urological work‐up should be maintained for recurrent genitourinary symptoms in these patients.